Long Wavelength Plasmonic Absorption Enhancement in Silicon Using Optical Lithography Compatible Core-Shell-Type Nanowires - Mohammed Shahriar Sabuktagin; Khairus Syifa Hamdan; Khaulah Sulaiman; Rozalina Zakaria; Harith Ahmad (International Journal of Photoenergy)
Plasmonic properties of rectangular core-shell type nanowires embedded in thin film silicon solar cell structure were characterized using FDTD simulations. Plasmon resonance of these nanowires showed tunability from  nm. However this absorption was significantly smaller than the Ohmic loss in the silver shell due to very low near-bandgap absorption properties of silicon. Prospect of improving enhanced absorption in silicon to Ohmic loss ratio by utilizing dual capability of these nanowires in boosting impurity photovoltaic effect and efficient extraction of the photogenerated carriers was discussed. Our results indicate that high volume fabrication capacity of optical lithography techniques can be utilized for plasmonic absorption enhancement in thin film silicon solar cells over the entire long wavelength range of solar radiation.